REAL DESCRIPTION REGARDING THE MANAGEMENT OF HUMAN RESOURCE AND TOURISM MARKETING AT MICRO, SMALL AND MEDIUM ENTERPRISES OF TOURISM SECTOR IN EAST JAVA - Hermawati, Adya; Ramlawati, Ramlawati; Husin, Husin; Nurwati, Nurwati; Martaleni, Martaleni (Jurnal Aplikasi Manajemen, 2021)
To analyze and obtain the real description regarding the management of human resource at Micro, Small and Medium Enterprises (MSMEs) of Tourism Sector, which is understood through five aspects, which respectively are Transglobal Leadership, Job Involvement, Quality of Work Life, Organizational Citizenship Behavior, and Human Resource Performance. besides that, it is also necessary to understand the management of tourism marketing, which is understood through two aspects, that are Responsibility Marketing and Competitive Sustainability Tourism. The population of this research includes all human resource personnel at MSMEs of the Tourism Sector and all foreign and domestic tourists in East Java. The sample in this study was 200 MSMEs of the Tourism Sector that are selected from 10 regions with tourism potentials in East Java Province. From each MSME, there are 4 employees and 3 tourists who are chosen as respondents. This research involved 800 employees and 600 tourists, either foreign or domestic. Analysis technique uses Biplot / Cluster Analysis, which is aimed to obtain real description concerning human resource management and tourism marketing management at MSMEs of Tourism Sector. The results show that MSMEs in the Tourism Sector with Transglobal Leadership competitive advantages are found in Sidoarjo, Kediri, Blitar, and Malang districts. The competitive advantage of Quality of Work Life is found in Malang City and Kediri City. The competitive advantage of Organizational Citizenship Behavior is in Pasuruan Regency. The competitive advantage in Human Resources Performance is in Batu City. The competitive advantage of Responsibility Marketing is in Pasuruan Regency. Competitive advantages in Competitive Sustainability Tourism are found in Pasuruan City and Blitar City. This study introduces an integrated holistic compilation of the theoretical concepts of human resource strategy and marketing strategies implemented through the concept of responsible tourism marketing, which is applied to the MSMEs in the Tourism Sector in East Java Province.